Gambaran Pengetahuan Lansia Tentang Pencegahan Hipertensi Di Posyandu Lansia Kelurahan Bangsal Kecamatan Pesantren Kota Kediri - Vivien Dwi Purnamasari (Universitas Pekalongan, 2022)
Introduction, Indonesia is a country that has a large area with a very large population. This is a challenge in itself for the achievement of the goals of welfare development through healthy Indonesia 2013, namely to increase awareness, willingness and ability to live healthy for everyone in order to realize an optimal degree of public health through the creation of an Indonesian society, nation and state which is characterized by its population living in a natural environment. and with optimal health behavior. The purpose of the study was to obtain a general description of the level of knowledge of the elderly about hypertension prevention at the Elderly Posyandu, Kelurahan Bangsal, Pesantren sub-district, Kediri City. In this case, the researcher only wants to know things related to the state of something. This study uses a descriptive research design that will measure/assess the knowledge of the elderly about hypertension prevention. The results, obtained an overview of the knowledge of the elderly about hypertension prevention in the posyandu for the elderly in the Bangsal sub-district of the pesantren of Kediri City with good knowledge of 17 people (31.5%), sufficient knowledge of 33 people (84%), less knowledge 4 people (7.4% ). The conclusion of this study is that most of the respondents have sufficient knowledge of 84%. It is hoped that this research will pay attention to the development of information, especially regarding knowledge of its relationship to hypertension. The Posandu for the elderly and the Puskesmas are to improve the ability of health workers to provide counseling or health education about the knowledge and attitudes of the elderly about preventing hypertension.